Cross-border student mobility and improvements in the philippine tertiary education program relevance and learning outcomes - Connie Bayudan-Dacuycuy; Paola Ellaine D. Luzon; Suzanne J. Zambrano (Philippine Institute for Development Studies (PIDS), 2024)
Mainly using qualitative data, this paper analyzes whether and how cross-border student mobility contributes to enhanced Philippine tertiary education programs. The paper recognizes that the intake of international students is a product resulting from cross-border and homebased internationalization initiatives that are mutually reinforcing to improve programs and learning outcomes. The intake of international students further improves home-based internationalization initiatives, thus creating a virtuous cycle of effective initiatives, relevant educational products, and increased foreign student intake. However, the virtuous cycle has yet to materialize in the country due to its weak presence in the international student market. Currently, the country's inbound students are limited to specific nationalities, fewer than in other destination countries, and largely facilitated by educational agencies. While the ultimate objective is to improve the higher education programs and learning outcomes for Filipino learners' benefits, an increasingly sustained market share of international students seeking the country for its high-quality instructions and relevant fields of interest is a validation that the country's internationalization efforts have paid off. To realize these, the paper forwards recommendations in the bigger context of sustaining an HEI ecosystem responsive to local and international standards.
Keywords: 330; quality in tertiary education; cross-border student mobility; internationalization; benchmarking; partnerships